Their Footprints Remain Biomedical Beginnings Across the Indo-Tibetan Frontier - McKay, Alex (IIAS Publications Series, 2007)
By the end of the 19th century, British imperial medical officers and Christian medical missionaries began to introduce Western medicine to Tibet, Sikkim and Bhutan. Their Footprints Remain uses archival sources, personal letters, diaries, and oral sources in order to tell the fascinating story of how this once-new medical system became imbedded in the Himalayas. Of interest to anyone with an interest in medical history and anthropology, as well as the Himalayan world, this volume not only identifies the individuals involved and describes how they helped to spread this form of imperialist medicine, but also discusses its reception by a local people whose own medical practices were based on an entirely different understanding of the world.